ATM and PRDM9 regulate SPO11-bound recombination intermediates during meiosis - Jacob Paiano (Nature Portfolio, 2020)
Recombination requires DNA break formation by SPO11, following which SPO11 is thought to be released. Here, the authors show that meiotic hotspots retain SPO11 through a recombination intermediate dependent on the methyltransferase PRDM9, and that the ATM kinase governs the release of SPO11.